Analisis Permasalahan Penelantaran Anjing dalam Perspektif Kesehatan dan Kesejahteraan - Bryan Sebastian Chen; Cindy Vesakha Lauren; Angeline Salim; Ferdy Anthonius; Christian Siregar (Universitas Pendidikan Mandalika, 2026)
Dog abandonment is a prominent problem within the Indonesian environment that continues to increase as time goes, which can affect the dynamics of the dog population and the spread of rabies disease there. This study aims to analyze the problem of dog abandonment from the perspective of health and welfare, alongside sustainable dog population control efforts in Indonesia. The research method in this study makes use of the qualitative method that comes in the form of a semi-structured interview conducted with the workers at the Maria Stray Home dog shelter. The information obtained from the interview will form the basis for the results of the analysis, which is accompanied by the incorporation of information from existing scientific articles on similar topics as supporting information. Results indicate that the cause of dog abandonment tends to stem from the owner's unwillingness to keep the dog, which may also be driven by other factors such as economic conditions. Results also found that abandonment damages the physical and mental health of dogs, and that it can also potentially endanger human health within the vicinity. Abandonment also causes poor welfare within a dog when viewed from the perspective of Five Freedoms and Five Domains. Results also found that dog abandonment contributes directly to the increase in the dog population and the spread of rabies, which proves the necessity to account for the phenomenon of dog abandonment as an effort to control the dog population and prevent the spread of rabies in the Indonesian environment.